Determination of cord blood lipid profile in neonates and its correlation with birth weight and maternal anthropometry - Mandraha, Shipra; Agrawal, Avyact; Talware, Vikas (Indian Journal of Child Health, 2018)
Introduction: Serum lipid disorders have their roots in childhood and atherogenic changes are postulated to originate early in life. Cord lipid profile is a useful tool in the earlier detection of babies at a higher risk. Objectives: The objectives of the study were to assess the early onset dyslipidemia by determining cord blood lipid profile in healthy term newborns and to compare the cord blood lipid profile between terms small for gestational age (SGA) and appropriate for gestational age (AGA) newborns. Materials and Methods: This prospective observational study was conducted from October 2013 to October 2014 in the Department of Pediatrics of a Tertiary Care Institution of Central India. All normal term newborns with gestational age between 37 and 42 weeks were included in the study. After thorough examination, their weight, length, and ponderal index (PI) were recorded. Cord blood was collected immediately after the delivery and cord lipid profile was measured. Data were recorded and correlated statistically. Results: Of 114 neonates, 71 were AGA, 40 were SGA, and three were large for gestational age. There were 59 (51.8%) female and 55 (48.2%) male neonates. Birth weight, length, gestational age, head circumference, and PI were significantly higher in AGA neonates than SGA neonates (p